2022
DOI: 10.1021/acs.analchem.2c00861
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Luminescence Aptasensor Based on Dual-Emissive Persistent Luminescent Nanoparticles for Autofluorescence- and Exogenous Interference-Free Determination of Trace Aflatoxin B1 in Food Samples

Abstract: Sensitive and accurate determination of aflatoxin B1 (AFB1) is of great significance to food safety and human health as it is recognized as the most toxic mycotoxin and carcinogenic. Herein, we report a ratiometric luminescence aptasensor based on dual-emissive persistent luminescent nanoparticles (PLNP) for the accurate determination of trace AFB1 in complex food samples without autofluorescence and exogenous interference. Dual-emissive PLNP ZnGa2O4:Cr0.0001 was prepared first and acted as the donor for energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Additional evaluation of the two methods was likewise performed using the classical Student t test, and t exp values were found to be less than 2.78 for all test results (Table S1). Last but not the least, a side-by-side comparison of the detection range of the sensor with previous reports found that the sensor had a wide dynamic response range with practicality compared to other efforts. , In addition, the sensor was expected to be of maximum utility in POC testing thanks to its freedom from expensive sensing device support and the involvement of well-educated testers.…”
Section: Results and Discussionmentioning
confidence: 88%
“…Additional evaluation of the two methods was likewise performed using the classical Student t test, and t exp values were found to be less than 2.78 for all test results (Table S1). Last but not the least, a side-by-side comparison of the detection range of the sensor with previous reports found that the sensor had a wide dynamic response range with practicality compared to other efforts. , In addition, the sensor was expected to be of maximum utility in POC testing thanks to its freedom from expensive sensing device support and the involvement of well-educated testers.…”
Section: Results and Discussionmentioning
confidence: 88%
“…The Food and Agriculture Organization (FAO) claims that up to 25% of agricultural products have been contaminated by mycotoxins . Nowadays, food contamination by aflatoxins is one of the significant food safety issues because aflatoxins are known to be potent human carcinogens . Recently, vegetable oils have been of high concern because the occurrence of AFB 1 in oil seeds is frequently reported, and AFB 1 cannot be removed during the manufacturing process. , Up to now, many countries have set the maximum limits for AFB 1 in various foods, including crop seeds, edible oils, cereals, and baby food. Therefore, the validation and quality assurance of the AFB 1 analysis in various food matrices are of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…4 Nowadays, food contamination by aflatoxins is one of the significant food safety issues because aflatoxins are known to be potent human carcinogens. 5 Recently, vegetable oils have been of high concern because the occurrence of AFB 1 in oil seeds is frequently reported, and AFB 1 cannot be removed during the manufacturing process. 6,7 Up to now, many countries have set the maximum limits for AFB 1 in various foods, including crop seeds, edible oils, cereals, and baby food.…”
Section: Introductionmentioning
confidence: 99%
“…The current detection strategies for CIT are based on thin-layer chromatography, high-performance liquid chromatography (HPLC) integrated with fluorescence, aptamer-based sensing, enzyme-based immunoassays, , and mass spectrometry. , CIT detection was made possible with maghemite or magnetic nanoparticles and silver nanoparticles using Mossbauer and Raman spectroscopy. , These techniques are time-consuming, expensive, and not readily accessible in rural areas. Moreover, sophisticated instruments are required for such detection strategies.…”
Section: Introductionmentioning
confidence: 99%